(untitled) (The Review of Diabetic Studies, 2025)
Diabetes mellitus poses a growing public health challenge in rural India, where limited access to healthcare infrastructure hinders early diagnosis and effective management. This paper explores the integration of digital health technologies with Light Gradient Boosting Machine (LightGBM), a powerful machine-learning algorithm, to enhance diabetes care in rural Tamil Nadu. By leveraging mobile health platforms, wearable sensors, and predictive analytics, the proposed framework aims to identify high- risk individuals, personalize treatment plans, and improve health outcomes.